The impact of obesity on cardiac surgery outcomes. Issue 10 (29th August 2018) - Vargo, Patrick R.; Steffen, Robert J.; Bakaeen, Faisal G.; Navale, Suparna; Soltesz, Edward G.
Abstract: Background: A survival benefit for obese patients has been observed in various medical and surgical populations. We examined the effect of obesity on outcomes after cardiac surgery from a large national database. Methods: A total of 6 648 334 adult patients were identified from the Nationwide Inpatient Sample who underwent cardiac surgery between 1998 and 2011, of who 598 450 were obese. Multivariable regression analysis and propensity score matching were used for comparisons of outcomes and costs. Results: In‐hospital mortality was 2.0% for obese patients versus 2.3% for non‐obese patients (odds ratio [OR] 0.89, 95% confidence interval [CI] 0.84, 0.94). Obese patients were at increased risk for acute renal failure (OR, 1.20; CI, 1.16, 1.23) and wound infection (OR, 1.29; CI, 1.18, 1.40), but less likely to require blood transfusion (OR, 0.96; CI, 0.94, 0.98). Mean length of stay was the same (8.7 days), with greater mean total charges for obese patients ($103 645 vs $101 763, P  < 0.001). Conclusion: Obesity is associated with lower in‐hospital mortality rates, but a higher incidence of acute renal failure and wound infections.